THE RELATIONSHIP BETWEEN GOAL-ORIENTATIONS AND SPORT COMMITMENT AMONG ATHLETES - Noshin Benar; Mohsen Loghmani (Kharkov National Pedagogical University, 2012)
The purpose of present study was exploring of relationship between goal-orientations and sport commitment among athletes and comparison of goal-orientations and sport commitment and their constructs based on gender and type of sports. Participants were 108 Iranian athlete (40 female and 68 male), who responded to Task and Ego Orientation in Sport Questionnaire (T.E.O.S.Q) and Sport Commitment Model (SCM) questionnaire. Data were analyzed by Pearson's correlation coefficient, Independent-Samples t-test, and One-way ANOVA at P=0.05. The findings indicated that there were positively and significantly association between constructs, including sport enjoyment, personal investment, social constraints, involvement opportunities, and social support, whereas, involvement alternatives and task-orientation had negatively and significantly association with sport commitment. Also, team and open-skilled sport athletes had sport commitment and ego-orientation more than individual and closed-skilled sport athletes. As well as, female's athletes had sport enjoyment and social support more than male's athletes. It is possible that task-oriented players are elite and expert athletes, because extend and develop their fundamental skills in one's sport by their task-orientate characteristic, and probably these players with these characteristics tendency to turnover until experience more situations. Thus, these players had a less sport commitment than amateur athletes. Also, gender and type of sport differences can be results of individual differences and nature of sports skills. Implications for goal-orientations and sport commitment and their impacts on athletes as well as future research directions are further discussed.